Ginsenoside Rg1 alleviates corticosterone-induced dysfunction of gap junctions in astrocytes. (17th August 2017) - Xia, Cong-Yuan; Chu, Shi-Feng; Zhang, Shuai; Gao, Yan; Ren, Qian; Lou, Yu-Xia; Luo, Piao; Tian, Man-Tong; Wang, Zhi-Qi; Du, Guo-Hua; Tomioka, Yoshihisa; Yamakuni, Tohru; et al.
Abstract: Ethnopharmacological relevance: Ginsenoside Rg1 (Rg1), one of the major bioactive ingredients of Panax ginseng C. A. Mey, has neuroprotective effects in animal models of depression, but the mechanism underlying these effects is still largely unknown Aim of the study: Gap junction intercellular communication (GJIC) dysfunction is a potentially novel pathogenic mechanism for depression. Thus, we investigated that whether antidepressant-like effects of Rg1 were related to GJIC. Materials and methods: Primary rat prefrontal cortical and hippocampal astrocytes cultures were treated with 50 μM CORT for 24 h to induce gap junction damage. Rg1 (0.1, 1, or 10 μM) or fluoxetine (1 μM) was added 1 h prior to CORT treatment. A scrape loading and dye transfer assay was performed to identify the functional capacity of gap junctions. Western blot was used to detect the expression and phosphorylation of connexin43 (Cx43), the major component of gap junctions. Results: Treatment of primary astrocytes with CORT for 24 h inhibited GJIC, decreased total Cx43 expression, and increased the phosphorylation of Cx43 at serine368 in a dose-dependent manner. Pre-treatment with 1 μM and 10 μM Rg1 significantly improved GJIC in CORT-treated astrocytes from the prefrontal cortex and hippocampus, respectively, and this was accompanied by upregulation of Cx43 expression and downregulation of Cx43 phosphorylation. Conclusion: These findings provide the first evidence indicating that Rg1 can alleviate CORT-induced gap junction dysfunction, which may have clinical significance in the treatment of depression. Graphical abstract: